Adult attachment anxiety is associated with night eating syndrome in UK and US-based samples: Two cross-sectional studies. (1st May 2022) - Wilkinson, Laura L.; Rowe, Angela C.; Douglas, Tanisha; Thirkettle, Martin; Nolan, Laurence J.
Abstract: Previous research has shown that "attachment anxiety" is a robust predictor of disinhibited eating behaviours and that this relationship is underpinned by difficulties in managing emotion. Night eating syndrome (NES), a proposed eating disorder characterized by evening hyperphagia, nocturnal awakenings to eat, and morning anorexia, is also associated with eating to manage emotion. Across two studies ( N  = 276 & N  = 486), we considered a relationship between attachment anxiety and NES. In Study 1, we hypothesised (pre-registered) that attachment anxiety would predict NES score and that this relationship would be mediated by disinhibited eating. Participants were asked to complete questionnaire measures of attachment orientation, disinhibited eating (emotional and uncontrolled eating) and NES. Our parallel mediation model confirmed a direct relationship between attachment anxiety and NES (p < .001) and showed an indirect path via both emotional (95% CI: 0.15–0.63) and uncontrolled eating (95% CI: 0.001–0.36). In Study 2, we showed that fear of negative evaluation of eating significantly mediated a reversed relationship between attachment anxiety and NES (95% CI: 0.02–0.04). Finally, across both studies we used a novel tool to assess "eating to cope". We showed a relationship with emotional eating but failed to show a robust relationship with NES. Attachment orientation may represent a potential intervention target for night eating syndrome. Future research should consider a longitudinal approach to strengthen our understanding of directionality amongst these factors.